Aruncin B: Synthetic Studies, Structural Reassignment and Biological Evaluation. Issue 65 (30th October 2017) - Ribaucourt, Aubert; Towers, Christopher; Josa‐Culleré, Laia; Willenbrock, Frances; Thompson, Amber L.; Hodgson, David M.
Abstract: A ring‐closing alkene metathesis (RCM)/ oxyselenation‐selenoxide elimination sequence was established to the sodium salts E ‐ and Z ‐25 of the originally proposed structure for the recently isolated cytotoxin aruncin B (1 ), as well as to the sodium salt Z ‐34 of a related ethyl ether regioisomer; however, none of their corresponding free acids could be obtained. Their acid sensitivity, together with detailed analysis of the spectroscopic data indicated that profound structural revision was necessary. This led to reassignment of aruncin B as a Z ‐γ‐alkylidenebutenolide Z ‐36 . Although a related RCM/ oxyselenation‐selenoxide elimination sequence was used to confirm the γ‐alkylidenebutenolide motif, a β‐iodo Morita‐Baylis–Hillman reaction/ Sonogashira cross‐coupling‐5‐ exo‐dig lactonisation sequence was subsequently developed, due to its brevity and flexibility for diversification. Aruncin B (36 ), together with 14 γ‐alkylidenebutenolide analogues, were generated for biological evaluation. Abstract : A journey from misassignment to diversity : Decomposition on acidification of the synthesised E‐ / Z ‐ Na salts of the originally assigned structure of the cytotoxin aruncin B suggested intrinsic instability of the postulated free acid structure and structural misassignment. The true structure of aruncin B was then revealed via total synthesis as a butenolide. The conciseness (4 steps) and flexibility of the route enabled analogue synthesis (14 examples), some displaying improved activity/selectivity.